Evaluation of thyroid micro-carcinoma using shear wave elastography: Initial experience with qualitative and quantitative analysis. Issue 137 (April 2021) - Tan, Shi; Sun, Peng-Fei; Xue, Heng; Fu, Shuai; Zhang, Zhi-Peng; Mei, Fang; Miao, Li-Ying; Wang, Xiao-Hua
Highlights: SWE can differentiate benign from malignant thyroid nodules, reducing unnecessary FNA. Perinodular stiffness has potential to improve diagnosis of thyroid nodules. Emax≥ 28.2 kPa was identified as the best cut-off for SWE measurements. Abstract: Purpose: We aimed to assess the diagnostic performance of shear wave elastography (SWE) to assess perinodular stiffness before fine needle aspiration (FNA) of thyroid nodules with a maximum diameter of 1.0 cm. Method: This retrospective study included 69 thyroid nodules in 68 patients who underwent conventional ultrasound and SWE before ultrasound-guided FNA or surgical excision. The stiffness of perinodular regions was evaluated using wave patterns. Quantitative SWE features were also assessed. Sensitivity, specificity, accuracy, and area under the receiver operating characteristic curve were calculated using conventional ultrasound and conventional ultrasound with SWE. Results: Of the 69 nodules, 57(82.6 %)were malignant and 12(17.4 %)were benign. The maximum elastic modulus (Emax) was higher for malignant nodules(P＜ 0.05). There was no significant difference in mean elastic modulus or minimum elastic modulus between malignant and benign nodules. The Emax≥ 28.2 kPa was the best cut-off value for malignant base on receiver operating curve. Perinodular stiffness was significantly greater for malignant nodules compared with benign nodules according to shear wave patterns. Compared with ultrasound alone, the rate of benign lesions recommended for FNA decreased from 75.0 % (9/12) to 25.0 % (3/12) with conventional ultrasound plus SWE. Conclusion: SWE provides quantitative and qualitative information when used with conventional ultrasound. SWE has the potential to reduce the number of unnecessary FNA procedures.